THE CONCEPT OF LAW AND LEGAL CULTURE - Luiza Djuraevna Tuganova (Bright Mind Publishing, 2025)
Any sphere must first serve for the development of society. Since the goal is clear, we can see that today the concepts of culture and law have developed in a way that is inextricably linked to one of the other, and that the views that these concepts do not disappear today are very important. Striving for the correct interpretation of the concept of democracy by the people will only pay off if it follows the existing legal norms in society. Moral relations, which exist in any views, should be brought up not only in the ethics of lawyers, but also in the behavior of a member of society.
Keywords: Society, culture, law, civilization, consciousness, democracy, traditions.